Respuesta :

Answer:

x = 4b / (2 + a - b)

Step-by-step explanation:

Given :

  • x (2 + a) = b(x + 4)

Distribute the terms on both sides :

  • x(2) + x(a) = b(x) + b(4)
  • 2x + ax = bx + 4b

Bring the x terms to one side :

  • 2x + ax - bx = bx + 4b - bx
  • 2x + ax - bx = 4b

Take x as a common factor on the left side :

  • x (2 + a - b) = 4b

Divide both sides by (2 + a - b) :

  • x (2 + a - b) / (2 + a - b) = 4b / (2 + a - b)
  • x = 4b / (2 + a - b)

Answer:

x = [tex]\frac{4b}{2+a-b}[/tex]

Step-by-step explanation:

x(2 + a) = b(x + 4) ← distribute parenthesis on both sides )

2x + ax = bx + 4b ( subtract bx from both sides )

2x + ax - bx = 4b ← factor out x from each term on the left side

x(2 + a - b) = 4b ← divide both sides by (2 + a - b)

x = [tex]\frac{4b}{2+a-b}[/tex]

ACCESS MORE